2005
DOI: 10.1111/j.1468-2982.2004.00849.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Nociceptin Levels are Reduced in Migraine without Aura

Abstract: It was demonstrated that both nociceptin, a novel opioid neuropeptide, and its receptor are present in trigeminovascular neurons. In an animal model nociceptin dose-dependently inhibited neurogenic dural vasodilatation. These results suggest that nociceptin may be involved in neurovascular headaches such as migraine. To test this hypothesis, we studied circulating nociceptin levels in 18 patients suffering from migraine without aura and in 24 controls. Headache-free migraineurs had significantly lower nocicept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 41 publications
0
18
0
1
Order By: Relevance
“…in the hypothalamus, the brainstem and the dorsal horn of the spinal cord (Bridge et al, 2003;Mollereau and Mouledous, 2000). NOP has multidirectional effects in the CNS, exerting algesic, hyperalgesic and analgesic properties, while in the PNS it displays antinociceptive effects (Ertsey et al, 2005;Giuliani et al, 2000;Meunier et al, 2000;Reinscheid et al, 2000). In tracing experiments with immunohistochemical visualization, NOP-ir fibres of trigeminal origin were detected in the dorsal horn of the cervical spinal cord (Marfurt and Del Toro, 1987).…”
Section: Nopmentioning
confidence: 97%
See 2 more Smart Citations
“…in the hypothalamus, the brainstem and the dorsal horn of the spinal cord (Bridge et al, 2003;Mollereau and Mouledous, 2000). NOP has multidirectional effects in the CNS, exerting algesic, hyperalgesic and analgesic properties, while in the PNS it displays antinociceptive effects (Ertsey et al, 2005;Giuliani et al, 2000;Meunier et al, 2000;Reinscheid et al, 2000). In tracing experiments with immunohistochemical visualization, NOP-ir fibres of trigeminal origin were detected in the dorsal horn of the cervical spinal cord (Marfurt and Del Toro, 1987).…”
Section: Nopmentioning
confidence: 97%
“…In this experimental set-up, intravenously administered NOP dose-dependently suppressed the neurogenic dural vasodilatation via NOP1 receptor activation (Bartsch et al, 2002). A clinical study of the circulating NOP revealed a lower plasma NOP level in migraine patients without aura during the headache-free period than in controls, and the level correlating with the attack frequency (Ertsey et al, 2005).…”
Section: Nopmentioning
confidence: 98%
See 1 more Smart Citation
“…May indicate impaired pineal function in migraine. Of note, melatonin infusion improved some migraine symptoms.Decreased nocturnal plasma melatonin levelsMigraine with and without aura compared to controlsPlasma RIATrait 153 When depressed patients excluded, decrease was significant only in females with migraine.Decreased plasma nociceptin levelsMigraine without aura compared to controlsPlasma assayState (during headache) and trait (interictal) 154 Levels are lower in migraineurs than controls interictally, and decrease further during first 3 hours of an attack. Correlate with frequency of attacks.…”
Section: Confirmed Biomarkers Of Migraine Biomarker Population Methomentioning
confidence: 99%
“…In spite of the growing evidence that N/OFQ has a signifi cant role in cardiovascular regulation, studies having been made so far have concentrated mainly on its function in pain sensation and its possible use as a novel analgesic (9). Given that our limited knowledge on the N/OFQ system is based on studies made on rodents, human physiology remains relatively unclear (8).…”
mentioning
confidence: 99%